2022
DOI: 10.1155/2022/2266951
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tungsten Carbide Addition on the Microstructure and Mechanical Behavior of Titanium Matrix Developed by Powder Metallurgy Route

Abstract: The ambition of this research work is to evaluate the hardness and wear behavior of titanium alloy reinforced with tungsten carbide particle (WC) composite prepared by powder metallurgy route. Titanium alloy with 5 and 10 wt% tungsten carbide reinforced particle (WC) composites was manufactured through powder metallurgy technique. The hardness and wear properties of the composite are measured in hardness and wear tests. The microstructures of the composite are evaluated by utilized optical microscopy. The fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The use of MMCs in diverse industries has increased significantly to meet the high demand in producing necessary and complex components for marine, aircraft, and automotive applications. Govindarajan et al [6] emphasized on the importance of MMCs in automobile industries since they play a critical role in offering a lightweight material exhibiting both high stiffness and sturdiness. Santhosh et al [7] reported that MMCs containing magnesium is potentially going to become one of the widely-used materials due to possessing higher energy efficiency as well as recyclability.…”
Section: Introductionmentioning
confidence: 99%
“…The use of MMCs in diverse industries has increased significantly to meet the high demand in producing necessary and complex components for marine, aircraft, and automotive applications. Govindarajan et al [6] emphasized on the importance of MMCs in automobile industries since they play a critical role in offering a lightweight material exhibiting both high stiffness and sturdiness. Santhosh et al [7] reported that MMCs containing magnesium is potentially going to become one of the widely-used materials due to possessing higher energy efficiency as well as recyclability.…”
Section: Introductionmentioning
confidence: 99%
“…These flakes with no plastic deformation at the edge and some fatigue cracks are found inside the flakes, indicating that the wear is a typical sign of fatigue spalling. Therefore, the wear mechanism of sample a is mainly adhesive wear and fatigue wear [53,54]. As shown in Figure 19(a3,b3), most of the cracks in the substrate extended very seriously and gathered at the spalling and flakes.…”
Section: Wear Performancementioning
confidence: 97%
“…The hardness is improved, and the coefficient of friction (COF) and wear rate are minimized when the tungsten carbide is added to the titanium alloy matrix [8,9]. Adding nano-sized particles as an adjuvant decreases agglomeration during material preparation [10]. Hence, in this research, nano-sized tungsten carbide is used as an additive element for improving the wear resistance of Al 4043 alloy.…”
Section: Introductionmentioning
confidence: 98%